تقويم أداء معلم العلوم للمرحلة المتوسطة بمحافظة ضرية فى ضوء المعايير المهنية للمعلمين بالمملكة العربية السعودية من وجهة نظر المعلم - أبو ثنتين، نواف رفاع مفرس (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2018)
استهدفت الدراسة الحالية تحليل المعايير المهنية للمعلمين بالمملكة العربية السعودية، وتعرف مدى توفر هذه المعايير في أداء معلم العلوم بمحافظة ضرية من وجهة نظرهم، وما العلاقة بين الأداء، وبين متغيرات: سنوات الخبرة، والنوع (ذكر/أنثي). استخدام الباحث المنهج الوصفي لوصف وتحليل تلك المعايير، وتوصل إلى عبارات تمثل ممارسات المعايير الثمانية، ثم حول هذه العبارات إلى استبانة تكونت من (89) ممارسة لاستخدامها في جمع البيانات الكمية عن مدى توافر تلك المعايير في أداء معلمي العلوم. تكونت عينة الدراسة الميدانية من (32) معلم ومعلمة (منهم (18) معلم و(14) معلمة) من معلمي العلوم بمحافظة ضرية، وهذا ما يمثل نسبة (50%) من مجتمع الدراسة، ثم طبق الباحث أداة الدراسة، وتوصل إلى النتائج التالية: 1-نسبة تحقق الاستبانة ككل (كل المعايير) كانت 61.65%، وهي نسبة متوسطة. 2-جاءت المجالات بالترتيب التالي: أ-المجال الأول "القيم والمسؤوليات المهنية" وتحقق بنسبة 64.36% وهي نسبة متوسطة. ب-المجال الثاني "المعرفة المهنية للمعلمين" وتحقق بنسبة 60.81% وهي نسبة متوسطة. ج-المجال الثالث "الممارسة المهنية للمعلمين" وتحقق بنسبة 59.79% وهي نسبة متوسطة. 3-هناك فروق تعود إلى الخبرة، حيث ذوي الخبرة الأقل من (8) سنوات كانت 76%، وهي نسبة جيدة وذوي الخبرة أكثر من (8) سنوات كانت 54%، وهي نسبة متوسطة. 4-هناك فروق طفيفة تعود إلى النوع، حيث كانت للإناث 63%، وللذكور 67%. من خلال النتائج قدمت الدراسة توصيات مثل: 1-نشر ثقافة التقييم على أساس المعايير وعمل دورات تدريبية للتعريف بالمعايير المهنية للمعلمين. 2-نشر ثقافة التقييم الذاتي بين المعلمين. 3-الترخيص الدوري لمزولة مهنة التدريس وفق المعايير المهنية للمعلمين. The current study aimed to analyze the professional standards for teachers, Saudi Arabia, and determine the availability of these standers in the performance of Dariyah Governorate science teacher, from their perspective, and what is the relationship between the performance and variables years of experience, and gender (male / female). The researcher has used the descriptive approach to descript and analyze this professional standards. The researcher has formulated a list of phrases represent the practices of (8) standards, after that, he changes this phrases to a questionnaire consisted of (89) Practices to use it to combine quantitative data about the availability of these standers in the performance of science teachers. The sample of the field study consisted of (32) teachers (18 male & 14 female) of science teachers work in Dariyah Governorate, this represents the proportion (50%) of the study population. Then, the researcher has applied the study tool, and reaches the following results: 1-The proportion of check questionnaire (all standards) was (61.65%), and this was a medium ratio. 2-The domains taked the following order: a- The 1st domain, "Professional responsibilities and values" in the 1st order by 64.36%, and this was a medium ratio. b- The 2nd domain, "Professional knowledge for teachers" in the 2nd order by 60.81%, and this was a medium ratio. c. The 3rd domain, "Professional practice for teachers" in the 2nd order by 59.79%, and this was a medium ratio. 3There were differences due to experience, where experienced less than (8) years was76 %, and this was a good ratio, and experienced more than (8) years was 54 %, and this was a medium ratio. 4There are slight differences due to gender, where male was 67% and female was 63%. The study results provided recommendations as: 1-Spread the culture of evaluation based on standards and make training courses for the definition of professional standards for teachers 2-Spread the culture of self-assessment among teachers 3- Periodic licenses for practicing teaching profession according to the professional standards for teachers
Keywords: الأداء التربوى -- معلمو المرحلة المتوسطة -- المعايير التربوية -- الكفاءة المهنية -- محافظة ضرية -- السعودية